COGNITIVE SCIENCE, CONTINUOUS CREATION, AND ZYGON MOVING ON. - Petersen, Arthur C. (Zygon: Journal of Religion & Science, 2020)
The "Cognitive Science of Religion" and, more broadly, the new scientific study of religion, have been in the ascendant for several decades now. Will Mason-Wilkes analyzes film sequences focusing on DNA in two BBC nonfiction science television programs and identifies contrasting "religious" and "secular" representations of science. The new Joint Publication Board (its Board of Directors) is composed of three members each from the two original sponsoring organizations of the journal, the Institute on Religion in an Age of Science (IRAS) and the Center for Advanced Study in Religion and Science (CASIRAS), and from a third sponsoring organization, the International Society for Science and Religion (ISSR).